Physical Activity, Sitting Time, and Feelings of Energy and Fatigue During the Early Stages of the COVID-19 Pandemic: Does Grit Make a Difference? - Andreas Stamatis; Jessica Adams; Joel Martin; Matthew L. Smith; Italia Milani; Shane V. Caswell; Nelson Cortes; Ali Boolani (New Prairie Press, 2022)
Grit has been associated with feelings of energy when measured as the opposite end of fatigue. During the COVID-19 pandemic, grit has been linked to positive health-related behaviors, which are known to influence feelings of energy and fatigue. The objective of this study was to identify the association between grit, time spent sitting, physical activity (PA), and feelings of mental and physical energy (ME, PE) and fatigue (MF, PF) during the early stages of the COVID-19 pandemic in the United States. Participants (n = 859) completed surveys once. Using a series of multivariate regression models, we assessed the association between grit, time spent sitting, PA and ME, MF, PE, and PF. When accounting for all factors, performing vigorous PA was associated positively with PE and ME and negatively with PF and MF, whereas sitting was related negatively with PE and ME and positively with PF and MF. Grit was not associated with the four moods. Study findings underscore the need to adopt healthy lifestyle behavior to improve feelings of energy and fatigue in the face of a pandemic. During this ongoing global health crisis, these findings present novel and important evidence with possible immediate applications for health behavior, such as informing already-established health behavior theories to, ultimately, design COVID-19-specific interventions.